2018
DOI: 10.1016/j.ijsu.2018.03.080
|View full text |Cite
|
Sign up to set email alerts
|

Acquiring basic and advanced laparoscopic skills in novices using two-dimensional (2D), three-dimensional (3D) and ultra-high definition (4K) vision systems: A randomized control study

Abstract: The 4K vision system improved accuracy in acquiring laparoscopic skills for novices in complex tasks, which was shown in significant reduction in number of errors compared to the 3D and the 2D vision systems. The 3D and the 4K vision systems significantly improved speed and accuracy when compared to the 2D vision system based on shorter performance time, fewer errors and lesser number of repetitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…Cutting edge technologies like 4K ultra HD allow the surgeon to be even more minimally invasive. Abderlahman et al reported on the importance of the quality of 4K ultra HD images in reducing mistakes in structure identification 1 . Moreover, during left sided colorectal laparoscopic procedures, a precise visualization of the autonomic nerves is related to a better preservation of the genitourinary function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutting edge technologies like 4K ultra HD allow the surgeon to be even more minimally invasive. Abderlahman et al reported on the importance of the quality of 4K ultra HD images in reducing mistakes in structure identification 1 . Moreover, during left sided colorectal laparoscopic procedures, a precise visualization of the autonomic nerves is related to a better preservation of the genitourinary function.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic surgery provides several intra-and post-operative advantages such as improved cosmesis, less post-operative pain and faster recovery compared to open surgery 1 . The development of new technologies has allowed laparoscopic surgery to become faster and safer.…”
Section: Introductionmentioning
confidence: 99%
“…Six parameters were collected for analysis (suture time, thread length, accuracy of needle entry, stability of the knot, tissue integrity and tightness of the tissue), and the suture time was used for sample size calculation. Accoring to a similar research [ 10 ], a calculation with the width of the 95% confidence interval and an alpha level of 0.05 was performed, indicating that a minimum of 18 participants were required in each group to show a significant difference. The data are presented as the mean ± SD.…”
Section: Methodsmentioning
confidence: 99%
“…The new laparoscopic platforms together with the new generation of optics allow exceeding the limits of the two-dimensional (2D) view. Abdelrahman et al [61] reported that three-dimensional (3D) optics with ultrahigh definition 4k allow a faster learning curve. This experimental evidence was confirmed by Currò et al [62] , who concluded that the 3D vision improves the depth of perception, which is especially useful in performing an IA, and it also produces less physical strain to the surgeon.…”
Section: Three-dimensional Versus Two-dimensional View In Lrcmentioning
confidence: 99%